2023
DOI: 10.1093/toxres/tfad059
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic dye malachite green found in food induces cytotoxicity and genotoxicity in four different mammalian cell lines from distinct tissuesw

Andryo O de Almada Vilhena,
Karina M M Lima,
Luana F C de Azevedo
et al.

Abstract: Malachite green (MG) is a synthetic dye that uses ranges from its application as a tissue dye to that as an antiparasitic in aquaculture. Several studies have reported the presence of this compound in food dyes and in the meat of fish raised in captivity for human consumption, suggesting risks both for the end user and for as those who handle these products because of MG toxic properties described in the literature. Here we evaluated the cytotoxic and genotoxic profiles of MG in four different cell lines (ACP0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…These data revealed the potential of Pseudomonas plecoglossicide MG2 as a MG biodegrader. In accordance with these results, Vilhena et al [ 46 ] found that MG showed high cytotoxicity effect against tested cell lines (ACP02, L929, MNP01, and MRC-5). They also reported that higher MG concentrations exhibited cell necrosis while lower MG concentrations induced opoptosis.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…These data revealed the potential of Pseudomonas plecoglossicide MG2 as a MG biodegrader. In accordance with these results, Vilhena et al [ 46 ] found that MG showed high cytotoxicity effect against tested cell lines (ACP02, L929, MNP01, and MRC-5). They also reported that higher MG concentrations exhibited cell necrosis while lower MG concentrations induced opoptosis.…”
Section: Resultssupporting
confidence: 60%
“…There are many reports about the cytotoxicity effect of MG against cells from different organism including humans. In addition, carcinogenesis, teratogenesis, and mutagenesis potential of MG were reported in the human cells [ 46 ]. Despite its high toxicity, genotoxicity and carcinogenicity, MG is currently used extensively worldwide for dyeing due to its relatively low cost [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic products, renowned for their abundance in various unsaturated fatty acids and high-quality protein content, are susceptible to transmitting harmful substances to humans due to the distinctive nature of their growth environments, distinguishing them from other edible products . Malachite green (MG), a common pollutant in aquatic environments, poses a significant health risk as it accumulates in the human body through the food chain, displaying pronounced toxicity, particularly toward the liver and other cells. , Enzymatic degradation of MG has attracted attention as a relatively efficient, environmentally friendly, and economical degradation method. , …”
Section: Introductionmentioning
confidence: 99%
“…MG is generally used in agriculture, aquaculture, food, health, textile, and other industries for a variety of purposes . It is highly carcinogenic to aquatic organisms such as fish and mammals. MG is a nonbiodegradable compound that is highly toxic by nature, persists in the environment for long periods of time, and penetrates the food chain. , Its toxicity increases with exposure time, temperature, and concentration and can induce carcinogenic, mutagenic, chromosome breaking, respiratory toxicity, etc. , Therefore, it is highly necessary to explore a simple method to modulate the toxicity of MG.…”
Section: Introductionmentioning
confidence: 99%